Safety of uranium fuel fabrication facilities : specific safety guide (International Atomic Energy Agency, 2010)
This safety guide supplements the safety requirements publication, Safety of fuel cycle facilities, and addresses all the stages in the life cycle of uranium fuel fabrication facilities (UFFFs), with emphasis being placed on design and operation. It describes the actions, conditions and procedures for meeting safety requirements and deals specifically with the handling, processing and storage of low enriched uranium that has a 235U concentration of no more than 6%, derived from natural, highly enriched or reprocessed uranium. The publication is intended to be of use to designers, operating organizations and regulators to ensure the safety of UFFFs.--Publisher's description.
"IAEA safety standards for protecting people and the environment."
"May 2010."
Keywords: Nuclear facilities -- Safety measures.; Uranium as fuel.; elektronické knihy; electronic books